CULTURAL IDENTITY REFLECTED IN ENGLISH AND RUSSIAN IDIOMS - Tohirova Sevinchoy; Shodiyeva Mushtariybonu; Ro’zimova Rayhona; Tursunbayeva Go’zal (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This research examines the concept of cultural identity as reflected in English and Russian idioms through a comparative linguistic and psychological approach. Idioms serve not only as expressive elements of language but also as cultural markers that reveal national mentality, traditions, and value systems. The study aims to identify similarities and differences in how cultural identity is encoded in idiomatic expressions of both languages. Special attention is given to the influence of historical background, social norms, and environmental factors on the formation of idioms. By analyzing selected idioms, the research demonstrates how language reflects culturally specific ways of thinking and perception. The findings suggest that while some idioms share universal human experiences, many are deeply rooted in unique cultural contexts. Thus, idioms function as an important tool for understanding intercultural communication and cultural psychology, highlighting the intricate relationship between language and identity.